The book that broke the world - Lawrence, Mark, 1966- (Lawrence, Mark, 1966- Library trilogy, 2024)
"The Library of Alexandria died in fire. Others fade away with less drama, ignored, forgotten, left to dust. To the athenaeum though, the great library of which all others are echoes, fires are merely a temporary inconvenience. The only true threat to the library's existence is a book--the one Livira wrote. Livira's book also brought her together with Evar, a young man who was raised in the library itself, and they discovered secrets that no one else had uncovered. But now they are separated--and something hunts them both."--